Chemical composition, insecticidal and biochemical effects of Melaleuca alternifolia essential oil on the Helicoverpa armigera. (19th April 2017) - Liao, M.; Xiao, J.‐J.; Zhou, L.‐J.; Yao, X.; Tang, F.; Hua, R.‐M.; Wu, X.‐W.; Cao, H.‐Q.
Abstract: Pesticide resistance has developed as a result of long‐term and extensive use of chemical pesticides. Essential oils from aromatic plants may provide a new and safe alternative to conventional insecticides. In this study, the insecticidal activities of the essential oil of Melaleuca alternifolia and their chemical constituents against Helicoverpa armigera Hubner were investigated, and the underlying mechanisms were studied. The essential oil showed distinct antifeedant (AFC50 = 8.93 mg/ml) and good contact (LD50 = 50.28 μg/larva) activities against H. armigera at 24 hr. Ten chemical components were identified using a gas chromatograph/mass spectrometer, and mainly included terpinen‐4‐ol (40.09%), γ‐terpinene (21.85%), α‐terpinene (11.34%), α‐terpineol (6.91%), α‐pinene (5.86%), terpinolene (3.24%) and 1, 8‐cineole (1.83%). Among them, five components were determined and results showed that these constituents possessed obvious antifeedant activities. The activities of acetylcholinesterase and glutathione S‐transferase were notably inhibited by the essential oil, as compared with the control, with strong dose‐ and time‐dependent effects. The results provide a basis for their development and utilization in the control of insects in the future.